Effect of the development of the banking system on economic growth in Libya (Al-Mukhtar Journal of Economic Sciences, 2023)
This study aims to investigate an effect of the development of the banking system on economic growth in Libya, through an econometric study in which the Autoregressive Distributed Lag (ARDL) method was used, applied to annual time series during the period from 1990 to 2020, Where a gross domestic product was used as  a dependent variable representing economic growth, while a  total credit granted by commercial banks to the private sector and total deposits in Libyan commercial banks were used as a percentage of the gross domestic product and net foreign assets as a percentage of the gross domestic product as independent variables representing indicators for the development of the banking system. Results of the study showed that there was a positive relationship between deposits and net foreign assets and economic growth, while the study indicated that there was an inverse relationship between the credit granted to the private sector and economic growth. And giving greater importance to the orientation credit to the private sector, especially small and
Keywords: : banking system; economic growth; net foreign assets; deposits; ARDL model